A New Architectural Perspective on Wind Damage in a Natural Forest - Jackson, Tobias; Shenkin, Alexander; Kalyan, Bavisha; Zionts, Jessica; Calders, Kim; Origo, Niall; Disney, Mathias; Burt, Andrew; Raumonen, Pasi; Malhi, Yadvinder (Frontiers in Forests and Global Change, 2019)
Wind damage is a significant driver of forest structure, ecology and carbon cycling in both temperate and tropical regions, but most of the literature on wind damage focusses on conifer plantations. Previous studies in broadleaf forests have been limited by a lack of data on tree architecture, a problem that is potentially overcome by terrestrial laser scanning. Here we apply novel approaches to estimate the critical wind speeds at which trees will break in a temperate, deciduous forest plot in Wytham Woods, UK, using a combination of field data and finite element analysis. Ash trees (Fraxinus excelsior) tend to have lower critical wind speeds than sycamores (Acer pseudoplatanus), while English oak (Quercus robur) are the most mechanically robust. This difference in critical wind speed is driven by tree size and architecture, rather than material properties. We observe a trade-off between critical wind speed and growth rate, both within and across species. Our estimates of critical wind speeds from field data are lower in summer than in winter, emphasizing the importance of the spring and autumn transition periods. Of the three species we studied, those with lower critical wind speeds drop their leaves earlier in autumn, suggesting that the timing of leaf shedding may be under selection pressure to minimize risk of tree damage from winter storms. These results are tentative, but also intriguing and intuitive.